(untitled) (New York, NY, 2003)
This is a very useful resource for students of basic medical science to use to help in synthesizing material with clinical information. The basic knowledge of bacteria, viruses, etc., should stimulate the intellectual curiosity of students to apply their knowledge in the clinical arena. The updated edition is certainly justified.
Keywords: Medical microbiology,Communicable diseases